Del(18p) shown to be a cryptic translocation using a multiprobe FISH assay for subtelomeric chromosome rearrangements. - Horsley, S; Knight, S; Nixon, J; Huson, S; Fitchett, M; Boone, R; Hilton-Jones, D; Flint, J; Kearney, L (1998)
We have previously described a fluorescence in situ hybridisation (FISH) assay for the simultaneous analysis of all human subtelomeric regions using a single microscope slide. Here we report the use of this multiprobe FISH assay in the study of a patient whose karyotype was reported by G banding analysis as 46,XX,del(18)(p11.2). Although the proband had some features suggestive of a chromosomal abnormality, relatively few of the specific features of del(18p) were present. She was a 37 year old female with mild distal spinal muscular atrophy (SMA), arthritis of the hands, an abnormal chest shape (pectus excavatum), and an unusual skin condition (keratosis pilaris). Reverse chromosome painting with degenerate oligonucleotide primer-polymerase chain reaction (DOP-PCR) amplified del(18p) chromosomes as a probe confirmed the abnormality as del(18p), with no evidence of any other chromosome involvement. Subsequently, the multiprobe FISH assay confirmed deletion of 18p subtelomeric sequence. However, the assay also showed that sequences corresponding to the 2p subtelomeric probe were present on the tip of the shortened 18p. The patient is therefore monosomic for 18p11.2-pter and trisomic for 2p25-pter, and the revised karyotype is 46,XX,der(18)t(2;18)(p25; p11.2). We believe that a proportion of all cases reported as telomeric deletions may be cryptic translocations involving other chromosome subtelomeric regions. Further studies such as this are necessary to define accurately the clinical characteristics associated with pure monosomy in chromosomal deletion syndromes.